Molecular Epidemiology of Human Intestinal Amoebas in Iran - M Rezaian; P Rostamkhani; H Hooshyar (Tehran University of Medical Sciences, 2012)
Many microscopic-based epidemiological surveys on the prevalence of human intestinal pathogenic and non-pathogenic protozoa including intestinal amoeba performed in Iran show a high prevalence of human intestinal amoeba in different parts of Iran. Such epidemiological studies on amoebiasis are confusing, mainly due to recently appreciated distinction between the Entamoeba histolytica, E. dispar and E. moshkovskii. Differential diagnosis can be done by some methods such as PCR-based methods, monoclonal antibodies and the analysis of isoenzyme typing, however the molecular study of these protozoa in Iran is low. Based on molecular studies, it seems that E. dispar is predominant species especially in the central and northern areas of Iran and amoebiasis due to E. histolytica is a rare infection in the country. It is suggested that infection with E. moshkovskii may be common among Iranians. Considering the importance of molecular epidemiology of amoeba in Iran and also the current data, the present study reviews the data currently available on the molecular distribution of intestinal human amoeba in Iran.